Inactivation of Chloramphenicol and Florfenicol by a Novel Chloramphenicol Hydrolase - Tao, Weixin (American Society for Microbiology, 2012)
Chloramphenicol and florfenicol are broad-spectrum antibiotics. Although the bacterial resistance mechanisms to these antibiotics have been well documented, hydrolysis of these antibiotics has not been reported in detail. This study reports the hydrolysis of these two antibiotics by a specific hydrolase that is encoded by a gene identified from a soil metagenome. Hydrolysis of chloramphenicol has been recognized in cell extracts of Escherichia coli expressing a chloramphenicol acetate esterase gene, estDL136. A hydrolysate of chloramphenicol was identified as p-nitrophenylserinol by liquid chromatography-mass spectroscopy and proton nuclear magnetic resonance spectroscopy. The hydrolysis of these antibiotics suggested a promiscuous amidase activity of EstDL136. When estDL136 was expressed in E. coli, EstDL136 conferred resistance to both chloramphenicol and florfenicol on E. coli, due to their inactivation. In addition, E. coli carrying estDL136 deactivated florfenicol faster than it deactivated chloramphenicol, suggesting that EstDL136 hydrolyzes florfenicol more efficiently than it hydrolyzes chloramphenicol. The nucleotide sequences flanking estDL136 encode proteins such as amidohydrolase, dehydrogenase/reductase, major facilitator transporter, esterase, and oxidase. The most closely related genes are found in the bacterial family Sphingomonadaceae, which contains many bioremediation-related strains. Whether the gene cluster with estDL136 in E. coli is involved in further chloramphenicol degradation was not clear in this study. While acetyltransferases for chloramphenicol resistance and drug exporters for chloramphenicol or florfenicol resistance are often detected in numerous microbes, this is the first report of enzymatic hydrolysis of florfenicol resulting in inactivation of the antibiotic.